2017
DOI: 10.1002/2017ja023898
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of electric fields' amplitudes in Langmuir turbulence: A numerical simulation study

Abstract: A systematic study of the properties of Langmuir turbulence generated by electron beams via bump‐on‐tail instabilities in strongly nonhomogeneous plasmas is presented. A statistical analysis of the Langmuir waves' amplitudes using numerical simulations based on two theoretical models is performed: a dynamical one and a probabilistic one. The former describes the self‐consistent dynamics of wave‐particle and wave‐wave interactions. The latter is a modified version of the quasi‐linear theory. To analyze the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Whereas the PDFs calculated using the probabilistic model mentioned above [164] are consistent with those provided by the numerical simulations based on the dynamical model presented in this review [10,73], additional results have been obtained in the latter case. Figure 22 shows typical non-normalized probability distribution functions P log 10 |E| 2 and P (|E|) obtained as a function of log 10 |E| 2 and |E|, respectively, during the time interval ∆T, in the case of a quasi-homogeneous plasma with ∆n 0.001.…”
Section: Statistics Of Electric Fields' Amplitudessupporting
confidence: 81%
See 3 more Smart Citations
“…Whereas the PDFs calculated using the probabilistic model mentioned above [164] are consistent with those provided by the numerical simulations based on the dynamical model presented in this review [10,73], additional results have been obtained in the latter case. Figure 22 shows typical non-normalized probability distribution functions P log 10 |E| 2 and P (|E|) obtained as a function of log 10 |E| 2 and |E|, respectively, during the time interval ∆T, in the case of a quasi-homogeneous plasma with ∆n 0.001.…”
Section: Statistics Of Electric Fields' Amplitudessupporting
confidence: 81%
“…The statistical study of the electric fields' amplitudes is an additional tool to investigate Langmuir wave turbulence and, in particular, to understand the origin and the nature of the waveforms' modulations. Such works were performed using experimental data or owing to numerical simulations, for conditions typical of the solar wind [73,154,155], the Earth electron foreshock [45,156] or the cusp regions [157]. For example, large scale simulations showed that the statistics of Langmuir wave fields can be substantially modified by the presence of inhomogeneities.…”
Section: Statistics Of Electric Fields' Amplitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…It predicted that the distribution of the amplitudes of the Langmuir waves in type III source regions should correspond to log-normal distribution. While some observations (Robinson et al 1993;Píša et al 2015) show good agreement with this prediction, there are numerous reports of observations and simulations (Krasnoselskikh et al 2007;Vidojevic et al 2012;Reid & Kontar 2017;Voshchepynets et al 2017) that show deviations of the distribution of the amplitudes of the Langmuir waves from log-normal can be rather significant.…”
Section: Introductionmentioning
confidence: 76%